Computer information systems and industrial management : 18th International Conference, CISIM 2019, Belgrade, Serbia, September 19-21, 2019, Proceedings /: 18th International Conference, CISIM 2019, Belgrade, Serbia, September 19-21, 2019, Proceedings. (2019) - Unknown
No abstract available